2014
DOI: 10.1007/s00122-014-2390-z
|View full text |Cite
|
Sign up to set email alerts
|

Stripe rust and leaf rust resistance QTL mapping, epistatic interactions, and co-localization with stem rust resistance loci in spring wheat evaluated over three continents

Abstract: In wheat, advantageous gene-rich or pleiotropic regions for stripe, leaf, and stem rust and epistatic interactions between rust resistance loci should be accounted for in plant breeding strategies. Leaf rust (Puccinia triticina Eriks.) and stripe rust (Puccinia striiformis f. tritici Eriks) contribute to major production losses in many regions worldwide. The objectives of this research were to identify and study epistatic interactions of quantitative trait loci (QTL) for stripe and leaf rust resistance in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 31 publications
1
62
1
Order By: Relevance
“…Epistasis has been shown to contribute substantially to the genetic variation for a number of complex traits (e.g., adaptation to drought, heat, and salinity) in crops including wheat and other cereals [62][63][64]. Therefore, the identification of epistatic QTLs is essential for the development of efficient marker-assisted selection (MAS) schemes for complex traits such as drought tolerance, aimed at improving breeding efficiency [65].…”
Section: Biparental Interval Mapping and Epistatic Qtlsmentioning
confidence: 99%
“…Epistasis has been shown to contribute substantially to the genetic variation for a number of complex traits (e.g., adaptation to drought, heat, and salinity) in crops including wheat and other cereals [62][63][64]. Therefore, the identification of epistatic QTLs is essential for the development of efficient marker-assisted selection (MAS) schemes for complex traits such as drought tolerance, aimed at improving breeding efficiency [65].…”
Section: Biparental Interval Mapping and Epistatic Qtlsmentioning
confidence: 99%
“…Currently, 73 formally and more than 10 temporarily designated Lr genes have been described for hexaploid wheat (McIntosh et al 2013;Buerstmayr et al 2014;Li et al 2014;Park et al 2014), and more than 80 leaf rust-resistance QTLs have been mapped (e.g., Buerstmayr et al 2014;Li et al 2014;Singh et al 2014;Tsilo et al 2014;Zhou et al 2014). QLr.cau-1AS was mapped on chromosome arm 1AS with the resistant allele being contributed by Luke.…”
Section: Discussionmentioning
confidence: 99%
“…This type of resistance is often quantified in the field by lower disease severity or smaller area under the disease progress curve (AUDPC) compared with a susceptible genotype, or in the greenhouse by longer latent period, smaller pustule size, lower pustule density, etc. Li et al (2014) provided a review about QTL for leaf rust-resistance in wheat published before 2013, summarizing about 80 QTLs assigned to 16 chromosomes, and additional QTLs were reported recently (e.g., Buerstmayr et al 2014;Singh et al 2014;Tsilo et al 2014;Zhou et al 2014). Slow-rusting resistance can be genetically mapped in chromosome regions delimited by DNA markers through QTL analysis, and it can be selected on the basis of tightly linked DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies revealed that the AUDPC in wheat crosses was controlled by additive dominance epistatic effect of two major genes plus polygene (Khan et al, 2009a). In QTLs mapping for leaf and stripe rust in wheat, Singh et al (2014) also identified several epistatic effects both for both rusts resistance QTL. In wheat cultivars, the AUDPC was controlled by three/four genes in cv.…”
Section: Discussionmentioning
confidence: 99%
“…In our continent, leaf and stripe rust affects the production on approximately 60 (63%) and 43 (46%) million hectares, respectively, if susceptible cultivars are grown (Singh et al, 2014). Due to the mutagenic nature of rust pathogens, new resistant cultivars are rendered susceptible after sometime and usually become ineffective (Ghaledozdani, 2005).…”
Section: Introductionmentioning
confidence: 99%